PENGARUH VARIASI PRODUK DAN CELEBRITY ENDORSEMENT TERHADAP MINAT BELI MAHASISWA UNIVERSITAS MATARAM PADA PRODUK SCARLETT WHITENING - Try Novianingsih; Junaidi Sagir; Hilmiati Hilmiati (Master of Management, Mataram University, 2023)
This study aims to examine the effect of product variety and celebrity endorsements on the buying interest of Mataram University students in Scarlett Whitening products. This research is a causal associative research (cause and effect) using primary data, the population used in this study were students from 10 faculties at the University of Mataram. The sampling technique used in this study was a non-probability sampling technique with a purposive sampling technique. With predetermined criteria, a sample of 104 respondents from 10 faculties at the University of Mataram was obtained. The data collection method in this study was an online survey by distributing online questionnaires via links that had been filled in with previous questions. The data analysis procedure uses Multiple Linear Regression Analysis. So the results of this study indicate that the variable Product Variation has a positive and significant effect on the buying interest of Mataram University students on Scarlett Whitening products, and the Celebrity Endorsement variable has a positive and significant effect on the buying interest of Mataram University students on Scarlett Whitening products.